The osmotic response of the Asian freshwater stingray (Himantura signifer) to increased salinity: A comparison with marine (Taeniura lymma) and Amazonian freshwater (Potamotrygon motoro) stingrays - Tam, W.L. (2014)
10.1242/jeb.00510